(untitled) (African Journal of Biomedical Research, 2020)
Catharanthus roseus belonging to family Apocynaceae is a plant with high medicinal importance and wide occurrence all over the world. It shows a number of therapeutic activities like antimicrobial, antidiabetic, anticancer, antiallergic, anti-inflammatory, cardioprotective activity etc. The present study is aimed to throw a light on the analysis and distribution of phytochemical constituents of C. roseus, transporters involved and influence of various factors on their abundance. A thorough analysis of the past and recent studies done in the field was made. C. roseus whole plant as well as individual parts contain diverse types of phytochemicals like alkaloids, phenols, saponins, tannins, terpenoids, steroids, flavonoids etc. The medicinal properties of C. roseus are attributed to the bioactivity of the above compounds. As the amount of phytochemicals extracted from the plant is less than the need, other different strategies like in-vitro cell culture technique, hairy root cultures, compost application, use of endophytes and arbuscular mycorrhizal fungi etc. should be employed to enhance the production of phytochemicals